2006
DOI: 10.1001/jama.296.15.1858
|View full text |Cite
|
Sign up to set email alerts
|

National Surveillance of Emergency Department Visits for Outpatient Adverse Drug Events

Abstract: Adverse drug events among outpatients that lead to emergency department visits are an important cause of morbidity in the United States, particularly among individuals aged 65 years or older. Ongoing, population-based surveillance can help monitor these events and target prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
511
2
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 768 publications
(540 citation statements)
references
References 39 publications
14
511
2
13
Order By: Relevance
“…Warfarin is a commonly prescribed drug with pharmacogenomic implications due to its narrow window for effectiveness and high incidence of bleeding complications [14]. The variability in warfarin response is partially due to genetic differences in the cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex subunit 1 (VKORC1) [15].…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Warfarin is a commonly prescribed drug with pharmacogenomic implications due to its narrow window for effectiveness and high incidence of bleeding complications [14]. The variability in warfarin response is partially due to genetic differences in the cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex subunit 1 (VKORC1) [15].…”
Section: Background and Significancementioning
confidence: 99%
“…Therefore, the implementation of personalized medicine has largely relied on mechanisms to collect and interpret large amounts of information through computerized systems, such as clinical decision support systems (CDSS); defined as any tool or system which provides filtered clinical and patient-related information to clinicians or patients in order to assist in patient care [10,11]. However, there have been limited assessments of CDSSs on perspectives, usability, and user satisfaction with no data available in pharmacists despite their role in personalized medicine [12,13].Warfarin is a commonly prescribed drug with pharmacogenomic implications due to its narrow window for effectiveness and high incidence of bleeding complications [14]. The variability in warfarin response is partially due to genetic differences in the cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex subunit 1 (VKORC1) [15].…”
mentioning
confidence: 99%
“…When a new drug is marketed, an active surveillance program might be established to monitor prospectively for safety signals that were too rare to appear in the typical clinical trial or, in some cases, to look for events that were hinted at in the clinical trials, but that did not have sufficient statistical power to definitively identify; this type of surveillance is drug-based. Certain settings like emergency departments (ED) can be used to look to see what drugrelated events are presenting to ED (15). Anaphylaxis is a good example of a critical event that would be seen in the ED and might be related to a drug.…”
Section: Active Surveillance and Other Enhanced Reporting Systemsmentioning
confidence: 99%
“…This data source can be used to identify new safety signals or can also provide information about the public health impact of know adverse events. A recent summary of this program's active surveillance findings for 2004 and 2005 showed that allergic reactions were the most common adverse event treated in EDs followed by unintentional overdoses (15).…”
Section: Enhanced Surveillance Based On Certain Settings National Elementioning
confidence: 99%
“…On average, 50% of older adults do not take their medications as prescribed (Haynes, McKibbon, & Kanani, 1996). Moreover, over one third of older adults' hospital admissions are due to adverse drug events, often reflecting medication misuse (Budnitz, Pollock, Weidenbach, Mendelsohn, Schroeder, & Annest, 2006). Among other factors, nonadherence has been linked to age-related differences in cognitive function and health literacy combined with inadequate collaboration between patients and providers, leading to calls to improve self-care by supporting patient/provider collaboration and planning (for review see Aspden, Wolcott, Bootman, & Croenwett, 2007).…”
mentioning
confidence: 99%